Stereopsis with TNO and Titmus Tests in Symptomatic and Asymptomatic University Students. - Momeni-Moghadam, Hamed; Kundart, James; Ehsani, Marzieh; Gholami, Khatereh (Journal of Behavioral Optometry, 2012)
Introduction: One factor in the evaluation of binocular vision is the measurement of stereopsis. Several methods are available for this purpose. The most common procedures are anaglyphic (with use of red-green filters) and vectographic (with use of polarized filters) procedures. The purpose of this study is the determination of stereopsis with local (Titmus) and global (TNO) tests in symptomatic and asymptomatic subjects with respect to type of disparity (crossed and/or uncrossed) in exophoric and esophoric subjects. Methods: In this cross-sectional study, 174 randomly selected students of Zahedan University of Medical Sciences served as subjects. Subjects were divided into symptomatic and asymptomatic groups according to the presence or absence of binocular vision symptoms. Dissociated heterophoria was determined with use of the alternate prism cover test and stereopsis with the TNO and Titmus tests. Results: The mean stereopsis with the TNO test in symptomatic and asymptomatic subjects with crossed disparity presentation of the stereo test was 133.1 ± 68.6 and 76.7 ± 81.9 sec arc, respectively. The stereopsis with the TNO test in symptomatic and asymptomatic subjects with uncrossed disparity presentation of the stereo test was 135.0 ± 66.0 and 83.2 ± 49.3 sec arc, respectively. With the Titmus test, the mean stereopsis with crossed disparity presentation of the stereo test in symptomatic and asymptomatic subjects was 44.3 ± 7.1 and 40.7 ± 3.3 sec arc, respectively, and with uncrossed disparity presentation of the stereo test 50.0 ± 11.8 and 40.0 ± 0.0 sec arc, respectively. The Mann- Whitney U test showed a statistically significant difference in stereopsis (with both presentations of the test) between the two groups (p<0.05). The difference in stereopsis between esophoric and exophoric subjects was between 30-60 arc seconds for global stereopsis, and less than 2 arc seconds for local stereopsis. Esophoric subjects generally had a higher threshold for symptoms. However, these differences were not statistically significant (p>0.05). The best cutoff points for distinguishing between symptomatic and asymptomatic subjects with the TNO and Titmus stereo tests were determined to be 90 and 45 seconds of arc, respectively. Conclusion: Stereopsis is a useful factor in distinguishing between symptomatic and asymptomatic individuals. For that purpose, a global test was more useful than a local test. Specifically, symptomatic subjects could be detected at a higher (90 arc sec) threshold with random-dot stereopsis than the 45 arc sec symptom threshold with Titmus-type stereopsis. Half of esophoric patients and only approximately a quarter of exophoric patients were symptomatic.